Invasiones en montañas: ¿Cuánto hemos avanzado en los últimos 10 años y cuáles son los desafíos para los ecosistemas de los Andes? - Fuentes Lillo, Eduardo; Pauchard, Aníbal (Gayana Botánica, 2020)
During the last decade, there has been a great interest in understanding the process of invasion of exotic plants in the ecosystems of the Andes mountain range, because they have a high diversity endemic species and are an important source of ecosystem services. Therefore, this review aims to assess the current state of knowledge about the invasion of plants in the mountain ecosystems of the Andes mountain range. Through a systematic quantitative review that I integrate publications made in the periods 1997-2017. The aim was to identify scientific productivity during the last 10 years, the main research trends and understand how global change processes will affect the invasion process. We determined that publications per year increase linearly (R2 = 0.68), being more noticeable during the last 10 years (2008-2017). More than 50% of the publications were concentrated in studies carried out in Andean ecosystems in Chile and Argentina. The most developed themes were new reports of exotic species (18.48%) and the study of anthropic disturbances as agents promoting invasion (16.38%). Based on the research patterns, it was exemplified how the anthropic factors model the patterns of distribution of exotic species in the ecosystems of the Andes and how the patterns of global change will have implications for the redistribution patterns of the exotic species. Finally, we conclude that it is necessary to strengthen experimental studies on climate change, impact assessment and the generation of control and management protocols for exotic species.